Neural correlates of decision making and executive function in suicidal thoughts and behaviors - Tian, Fangfang; Zhou, Lu; Wang, Xiuli; Roberts, Neil; Pang, Hua (Frontiers in Psychiatry, 2025)
BackgroundTo investigate the neural alterations associated with decision-making (DM) and/or executive function (EF) in psychiatric patients with suicidal thoughts and behaviors (STBs).MethodsSystematic searches for relevant publications were performed using the PubMed, ScienceDirect and Web of Science databases. A method of quantitative coordinate-based meta-analysis, known as anisotropic effect size version of seed-based d mapping (ASE-SDM), was used to locate brain regions displaying anomalous activations in patients with STBs compared to patient controls (PCs) based on DM and EF tasks, separately. Moreover, we used multimodal analysis to investigate the neural correlates of DM and EF tasks in the brain. Additionally, sensitivity analysis was conducted to assess the robustness of the results, and publication bias was evaluated to ensure the reliability of the findings.ResultsThe results pertaining to the DM tasks revealed significant hyper-activations of the left anterior cingulate cortex (BA 24, p = 0.000371) and right insula (p = 0.000640), together with hypo-activations of left insula (p = 0.000387) and left hippocampus (p = 0.0000619) in patients with STB compared to PCs. During the EF tasks, patients with STB only showed hyper-activations in the left anterior cingulate cortex (BA 24, p = 0.00121) and left precentral gyrus (p = 0.00391) compared to PCs. The multimodal analysis elucidates the significance of the cingulate cortex in both DM and EF processes.ConclusionsOur results suggest that dysregulated neural activity of the ACC is a key mechanism contributing to suicidal risk, with DM abnormalities playing a more central role than EF deficits. These findings highlight potential targets for interventions, such as cognitive-behavioral therapies focusing on DM and impulsivity, or targeting the shared brain region in the left ACC, which could reduce suicidal behavior. Addressing emotional regulation through mindfulness-based therapies may also be beneficial. Future research should validate these interventions and explore their long-term efficacy. This study has been registered in PROSPERO (number CRD42022340922).